Is family sense of coherence a protective factor against the obesogenic environment?. (1st April 2016) - Speirs, Katherine E.; Hayes, Jenna T.; Musaad, Salma; VanBrackle, Angela; Sigman-Grant, Madeleine; ,
Abstract: Despite greater risk for poor nutrition, inactivity, and overweight, some low-income children are able to maintain a healthy weight. We explore if a strong family sense of coherence (FSOC) acts as a protective factor against childhood obesity for low-income preschool children. Families with a strong FSOC view challenges as predictable, understandable, worthy of engaging, and surmountable. Data were collected from 321 low-income mothers and their preschool children in five states between March 2011 and May 2013. FSOC was assessed using the Family Sense of Coherence Scale. A 16-item checklist was used to assess practicing healthy child behaviors (fruit and vegetable consumption and availability, physical activity, and family meals) and limiting unhealthy child behaviors (sweetened beverage and fast food consumption, energy dense snack availability, and screen time). Child body mass index (BMI) z-scores were calculated from measured height and weight. FSOC was significantly associated with practicing healthy child behaviors ( β = 0.32, p < .001). We did not find a statistically significant association between FSOC and limiting unhealthy child behaviors or child BMI z-scores in fully adjusted models. Our results suggest the importance of family functioning in predicting health behaviors around food consumption and availability, physical activity, and family meals. Highlights: Family sense of coherence (FSOC) explored as protective factor for child obesity. Positive association between FSOC and practicing healthy behaviors. FSOC and limiting unhealthy behaviors weakly related in unadjusted model. FSOC and limiting unhealthy behaviors not associated in adjusted models.